Student-centered teaching in private higher education institutions in Egypt - Aly, Soha Sayed Abdelhady (AUC Knowledge Fountain, 2017)
This study aims at assessing to which extent the teaching approach in private higher education institutions in Egypt employs a student-centered approach from the perceptions of students. This is to review the quality of teaching at those institutions which were originally established to contribute to overcoming the poor-quality issues of the Egyptian higher education sector. As Egypt still ranks very late in global higher education competitiveness, it is important to understand how those institutions are employing student-centered teaching to enhance quality of teaching and equip graduates with problem solving and critical thinking skills. A qualitative methodology was used through conducting fifteen in-depth interviews with undergraduate and graduate students from three foreign-affiliated private universities in Egypt. For conceptual clarity, the study used a framework developed by Weimer (2002, 2013) that provides five key dimensions for the student-centered teaching which are: 1) the role of the teacher; 2) the balance of power in the classroom; 3) the function of content; 4) the responsibility for learning; 5) the student-centered evaluation. The findings suggest that generally there is a lack of using such student-centered approach in private universities in Egypt as teachers were hardly to be perceived as facilitators, but rather largely depended on traditional lecturing and provided no or minimum room for discussions which mostly failed to engage students. This was also associated with clear control by teachers over the classroom environment, lack of interactions with students and lack of using feedback and self and peer-assessment. Thus, in some dimensions of teaching, student-centered features were evident as in using open-ended assignments, the practical nature of assignments using group projects and some teachers’ characteristics that encouraged students to assume responsibility for learning as consistency and deep knowledge of the subjects. Those institutions are therefore recommended to strategically plan and implement the shift towards a more student-centered approach that should enhance the teaching quality and the skills acquired by graduates.